2004
DOI: 10.1099/mic.0.26927-0
|View full text |Cite
|
Sign up to set email alerts
|

tvcp12: a novel Trichomonas vaginalis cathepsin L-like cysteine proteinase-encoding gene

Abstract: Trichomonas vaginalis is the causative agent of trichomoniasis, one of the most common sexually transmitted diseases in humans. This protozoan has multiple proteinases that are mainly of the cysteine proteinase (CP) type, some of which are known to be involved in the parasite's virulence. Here, a novel T. vaginalis CP-encoding gene, tvcp12, was identified and characterized. tvcp12 is 948 bp long and encodes a predicted 34·4 kDa protein that has the characteristics of the papain-like CP family. TvCP12 does not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 43 publications
1
46
0
2
Order By: Relevance
“…Garber et al (24) reported the cloning of a cDNA from a GT 11 library representing a portion of a secreted 60-kDa CP, whereas Leon-Sicairos et al (25,26) reported the cloning of three CPs, including an apparently intracellular CP, tvcp12. Although the approach used by Mallinson et al (7) to clone T. vaginalis CPs did not allow the investigators to identify the CPs as being secreted, our MALDI-TOF MS (Fig.…”
Section: T Vaginalis Infection Induces Apoptosis In Hvecs-mentioning
confidence: 99%
See 1 more Smart Citation
“…Garber et al (24) reported the cloning of a cDNA from a GT 11 library representing a portion of a secreted 60-kDa CP, whereas Leon-Sicairos et al (25,26) reported the cloning of three CPs, including an apparently intracellular CP, tvcp12. Although the approach used by Mallinson et al (7) to clone T. vaginalis CPs did not allow the investigators to identify the CPs as being secreted, our MALDI-TOF MS (Fig.…”
Section: T Vaginalis Infection Induces Apoptosis In Hvecs-mentioning
confidence: 99%
“…The other two are partial, although near fulllength. Subsequently, additional CPs were cloned by Garber et al (24) (accession number X70823) and Leon-Sicairos et al (25,26; accession numbers AY371180, AY371181, and AY463679).…”
mentioning
confidence: 99%
“…Ranging from 20 to 110 kDa (63), several of the lowermolecular-mass proteinases are released from the cell (63,64,81), although a recent report suggests that one cysteine proteinase is probably cytoplasmic since it lacks a signal peptide (60).…”
Section: Biochemistry Of Virulence and Pathogenesismentioning
confidence: 99%
“…We used the following primer pairs to amplify the 1320-bp mp50 gene: forward, 5Ј-CCGGATCCATGTCAGGTGAC-GAATTC-3Ј (BamHI recognition site is underlined) and reverse, 5Ј-CCAAGCTTTCAAAGTACTCTTGAAGC-3Ј (HindIII recognition site underlined). In addition, a 112-bp fragment of the ␤-tubulin gene was used as a loading control (20). The amplified products were analyzed on 1% agarose gels and visualized by ethidium bromide staining.…”
Section: Methodsmentioning
confidence: 99%